Ageing in place together: older parents and ageing offspring with intellectual disability. Issue 2 (12th February 2022) - Chou, Yueh-Ching; Kröger, Teppo
Abstract: Limited research has been conducted about ageing in place among older parents who co-habit with their ageing offspring with intellectual disability (ID). This study aims to explore which older parents would choose ageing in place together with their ageing offspring with ID instead of moving and what factors are associated with this choice. A face-to-face interview was conducted using the 'housing pathways' framework with older parents (⩾60 years) co-habiting with their ageing offspring with ID (⩾40 years) from two local authorities in Taiwan. In total, 237 families completed our census survey between June and September 2015. The results showed that 61.6 per cent of the participants would choose ageing in place with their ageing offspring with ID, while 38.4 per cent of the participants would stay in their previous place without their disabled children, move in with their other children or move to a nursing home. Logistic regression analyses revealed that parents who preferred ageing in place together with their offspring with ID were more likely to own a house ('personal control'), have higher levels of life satisfaction ('self-esteem') and satisfaction with their current community ('self-identity'), and have a lower level of social support than parents who chose another option. To meet the needs of older parents and their ageing offspring with ID, care and housing transitions should be considered as part of long-term care policy.